ARTERIAL HYPERTENSION STATISTICS AT THE LEVEL OF PRIMARY HEALTH CARE IN THE CITY OF BUKHARA - Ochilova Dilorom Abdukarimovna; Usmonov Ulugbek Rizoyevich (Research Parks Publishing LLC, 2020)
In article results of studying of prevalence and a condition of early diagnostics of hypertension among the population of Bukhara are given. High prevalence and insufficient diagnostics, cases of hyper diagnostics of hypertension among men and women is shown.